Children’s Questions and Answers of Parents: Sexual Education Dilemma - Alabay, Erhan; YAĞAN, SEVCAN (My University, 2018)
The main aim of this study is to determine questions of 36 to 72-month-old children have about sexuality and to examine the answers given by parents. In the first stage of the study, 84 parents were contacted in order to determine children’s most frequently asked questions on sexual development. In the second stage, top two questions from this list were selected and directed to 80 parents, all of whom were sampled from a separate pool. As a result of this study, it was discovered that children mostly question the physical features of girls and boys, and the pregnancy period. When parents' responses were examined, it was determined that a small portion of the responses were based on scientific grounds and that parents often provided answers based on avoidance-based and religious beliefs. Also, parents' gender, age, number of children, gender of their children, learning status and income do not make any difference.
Keywords: Preschool Period; Sexual Development; Sexual Education; Parent; Children; Okul Öncesi Dönem; Cinsel Gelişim; Cinsel Eğitim; Ebeveyn; Çocuklar